Un fiume per il territorio Indirizzi progettuali per il parco fluviale del Valdarno empolese - Magnaghi, Alberto; Giacomozzi, Sara (Territori, 2009)
This book illustrates the study carried out to define the project guidelines for the river park of the Arno and its tributaries the Pesa and the Elsa in the Empoli area, and has been produced by liaison between the territorial Planning Department and the Municipalities of the Empoli district. The integrated analysis of local resources scheduled, on the one hand the identification of the criticalities of the territorial system, and on the other the conscious and distinctly interpretational representation of the local cultural bedrock. The definition of scenarios for the entire territory has made it possible to demonstrate the outcomes of complex dynamics in a synthetic manner, moving on to the individual integrated projects and specific sectorial policies. It is precisely this recourse to scenarios, seen as the embodiment of a phase of project sharing and definition, that is the innovative feature of the «River Contract» proposed as a tool for the management and implementation of the plan.